Attitudes of Karak University College students towards distance learning during the Corona pandemic - Ala’a A. Al-Majali (دراسات: العلوم التربوية, 2023)
Objectives: The study aimed at identifying the level of students' attitudes towards distance learning in light of the Corona pandemic and detecting differences in students' attitudes towards the application of distance learning in light of the Corona pandemic.